Analysis of factors associated with the incidence of postpartum hemorrhage - Delfiani B.P; Muliyana; Yudiarsi Eppang; Suci Aulia Triastin (Ammar Dharma Foundation, 2024)
Background: One of the leading causes of maternal mortality in Indonesia in 2022 was postpartum hemorrhage, accounting for 741 cases. In addition to causing death, postpartum hemorrhage can lead to complications that affect the health of both the mother and baby in subsequent pregnancies and deliveries. Postpartum hemorrhage is a national-level issue and can be caused by several risk factors such as age, parity, and anemia.Objective: To analyze the factors associated with the incidence of postpartum hemorrhage.Research Method: This study employed a retrospective analytical method with a Case-Control Study approach, involving 71 postpartum mothers who experienced hemorrhage as cases and 71 postpartum mothers who did not experience hemorrhage as controls at RSUD Lamaddukkelleng Wajo from January 1 to December 31, 2023. Samples were selected using simple random sampling based on inclusion and exclusion criteria.Results: The Chi-Square statistical test results showed p-values for age (0.002 < 0.05), parity (0.001 < 0.05), and anemia (0.002 < 0.05). These results indicate a significant relationship between age, parity, and anemia with the incidence of postpartum hemorrhage.Conclusion: To reduce the Maternal Mortality Rate (MMR) due to postpartum hemorrhage, it is crucial for healthcare providers to improve the quality of care, especially for expectant mothers. By adopting a more comprehensive and preventive approach, we can identify and address risk factors early on, thereby reducing the incidence of postpartum hemorrhage and ensuring maternal safety. This effort will not only enhance overall maternal health but also strengthen the healthcare system's ability to effectively manage critical cases.